2022
DOI: 10.3389/fpls.2022.968719
|View full text |Cite
|
Sign up to set email alerts
|

Effects of AMF on plant nutrition and growth depend on substrate gravel content and patchiness in the karst species Bidens pilosa L

Abstract: Karst ecosystems represent a typical heterogeneous habitat, and it is ubiquitous with varying interactive patches of rock and soil associated with differential weathering patterns of carbonate rocks. Arbuscular mycorrhizae fungi (AMF) play an important role in regulating plant growth and nutrition in heterogeneous karst habitats. However, it remains unclear how AMF affects the growth and nutrition of plants in heterogeneous karst soil with varying patches and weathering gravel. A heterogeneous experiment with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 71 publications
1
9
0
Order By: Relevance
“…This evidence was strengthened by our study, where results from mycorrhized fruits showed evidence of improved levels of carotenoid and bioactive compound exclusively in sub-optimal fertility. In the light of this, we confirmed the plant stronger benefit from a symbiotic relationship with AMF in soil nutrient-scarce environments than in soil nutrientrich environments [56][57][58][59].…”
Section: Discussionsupporting
confidence: 69%
“…This evidence was strengthened by our study, where results from mycorrhized fruits showed evidence of improved levels of carotenoid and bioactive compound exclusively in sub-optimal fertility. In the light of this, we confirmed the plant stronger benefit from a symbiotic relationship with AMF in soil nutrient-scarce environments than in soil nutrientrich environments [56][57][58][59].…”
Section: Discussionsupporting
confidence: 69%
“…The plant community in areas has finally been replaced by B. pilosa [95]. The inoculation of AMF, Funneliformis mosseas, Diversispora versiformis, and Glomus diaphnum and/or G. etunicatum, increased the biomass and the absorption ability of nitrogen and phosphorus of B. pilosa in a karst environment [96,97]. The inoculation of Glomus mosseae also increased the drought stress tolerance of B. pilosa [98].…”
Section: Effects On Microbial Communitymentioning
confidence: 99%
“…According to the CSR theory of Grime (1977), the S strategy plants are mainly for survival by stress-tolerance in harsh habitat conditions, and the C strategy plants are mainly for conquest through competition due to scarce resources, while the R strategy plants are mainly for reproduction through increasing individuals of a population [2]. In particular, the karst maintains a lower resource of N and P and a barren soil layer with higher heterogeneous habitat [4,57,58], leading to adverse habitat conditions and scarce habitat resources. Therefore, competing for limited N and P resources through stress tolerance for individual survival is necessary as the optimal strategy of S with C in adverse karst habitats to maintain fewer family members.…”
Section: The Ecological Strategy In the Karst Forestsmentioning
confidence: 99%